Trustworthy and reliable computing using untrusted and unreliable quantum hardware - Upadhyay, Suryansh; Ghosh, Swaroop (Frontiers in Computer Science, 2024)
Security and reliability are primary concerns in any computing paradigm, including quantum computing. Currently, users can access quantum computers through a cloud-based platform where they can run their programs on a suite of quantum computers. As the quantum computing ecosystem grows in popularity and utility, it is reasonable to expect that more companies including untrusted/less-trusted/unreliable vendors will begin offering quantum computers as hardware-as-a-service at varied price/performance points. Since computing time on quantum hardware is expensive and the access queue could be long, the users will be motivated to use the cheaper and readily available but unreliable/less-trusted hardware. The less-trusted vendors can tamper with the results, providing a sub-optimal solution to the user. For applications such as, critical infrastructure optimization, the inferior solution may have significant socio-political implications. Since quantum computers cannot be simulated in classical computers, users have no way of verifying the computation outcome. In this paper, we address this challenge by modeling adversarial tampering and simulating it's impact on both pure quantum and hybrid quantum-classical workloads. To achieve trustworthy computing in a mixed environment of trusted and untrusted hardware, we propose an equitable distribution of total shots (i.e., repeated executions of quantum programs) across hardware options. On average, we note ≈ 30X and ≈ 1.5X improvement across the pure quantum workloads and a maximum improvement of ≈ 5X for hybrid-classical algorithm in the chosen quality metrics. We also propose an intelligent run adaptive shot distribution heuristic leveraging temporal variation in hardware quality to user's advantage, allowing them to identify tampered/untrustworthy hardware at runtime and allocate more number of shots to the reliable hardware, which results in a maximum improvement of ≈ 190X and ≈ 9X across the pure quantum workloads and an improvement of up to ≈ 2.5X for hybrid-classical algorithm.